Kemampuan Literasi Matematika Siswa SMP Ditinjau dari Perbedaan Kecerdasan Visual-Spasial - Yusril Rahmat Hidayat; Pradnyo Wijayanti (Program Studi S1 Matematika UNESA, 2023)
The capacity to formulate, apply, and understand mathematics in a variety of problem contexts is known as mathematical literacy. This study is a qualitative descriptive study that collects data from subjects consisting of one student with high visual-spatial intelligence, one student with moderate visual-spatial intelligence, and one student with low visual-spatial intelligence. The goal is to describe students' mathematical literacy in terms of visual-spatial intelligence differences. Mathematical literacy tests, interviews, and visual-spatial intelligence tests were all used in the study. The information is then researched by utilizing the stages of formulation, application, and interpretation of the mathematical process as defined by mathematical literacy. The results showed that students who had high visual-spatial intelligence were able to formulate by identifying the mathematical aspects of the problems obtained, able to design or use mathematical concepts to make strategies to get solutions to problems, and able to apply facts, rules and algorithms in solving problems, able in the process of interpreting by interpreting the results of the solution to the given problem. the mathematical literacy ability of visual-spatial intelligence students is able to formulate by identifying the mathematical aspects of the problems obtained, able to design and or use mathematical concepts to make strategies to obtain solutions to problems and be able to apply facts, rules and algorithms in solving problems, able to the process of interpreting by interpreting the results of the solution to a given problem. The mathematical literacy ability of students with low visual-spatial intelligence is less able to formulate, namely identifying the mathematical aspects in the problem, students are also lacking in interpreting the answers found whether they make sense to the problems at hand.